Factors associated with colonization by carbapenem-resistant enterobacteria in oncological patients: a case-control study - Moraes, Marina Araújo da Cruz; Sukiennik , Teresa Cristina Teixeira; Dias, Cícero Armídio Gomes (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Colonization and infections caused by Carbapenemase Producing Enterobacteria (CPE) are a global problem, being associated with an increase in hospitalization time, costs for health services, and morbidity and mortality rates. Oncologic patients represent a group of special interest and there are few studies involving CPE colonization among these patients. Aim: to investigate factors associated with colonization in cancer patients. Outlining: Case-control study developed in a tertiary reference hospital in cancer treatment in Porto Alegre, Brazil, from January to December 2017. The population consisted of patients diagnosed with cancer in clinical or surgical hospitalization. Results: The univariate analysis showed that variables associated with colonization by CPE were age, male sex, tumors with bone type of surgical hospitalization, number of intra-hospital transfers since hospitalization, hospitalization time >30 days, ICU hospitalization in the last 30 days, ICU time more than 15 days, surgical procedure in the last 30 days, use of antibiotics in the last 30 days, presence of tumor wound, and KPC infection. After multivariate analysis, male sex, external hospital as origin, hospital stay longer than 30 days, antibiotic use in the last 30 days, and presence of tumor wound, remained associated with EPC colonization. Use of aminoglycosides, and linezolide were associated with CPE colonization. Implications: We identified variables associated with CPE colonization in oncologic patients. Our results may indicate actions to prevent CPE colonization and consequent development of infections.